Mechanisms of Forming of Clinical Course Variants of Intestinal Infections in Infants - O.M. Olkhovska (Zaslavsky O.Yu., 2012)
In 81 children aged from 1 month to 3 years with severe forms of shigellosis, salmonellosis and colibacillosis there were studied the indices of immune response (cytokines and CD cells) depending on intensity and presence of main clinical symptoms of disease. Impact of immune factors on forming of toxic syndrome and exicosis, flaccidity, anorexia, vomiting, oliguria and ketoacidosis was discovered.